Cell biology and histology - Gartner, Leslie P. , 1943-; Hiatt, James L. , 1934- (Board review series, 2015)
"This updated Seventh Edition of BRS Cell Biology and Histology includes over 320 USMLE-style questions (with complete answers and explanations), and a comprehensive USMLE-format examination"--Provided by publisher